Piya Rang Kala - Yahya Khan, Muhammad; English Rendering by Ehsan, Ehsan Elahi, Prof. (Lahore Sang-e-Meel Publications, 2011)
Urdu Fiction.
Tapping into the power of spiritual world.
Keywords: Urdu Fiction -- Pakistani Fiction -- Pakistan